Study Of Reliability Of Smart Gates Based On IoT - Erwin; Solly Aryza; Adi Sastra Tarigan (INFOKUM, 2021)
This article describes the results of research on the design of a prototype device for an Arduino-based automatic gate control system and the Android operating system. The manufacture of tools is carried out as one of the efforts in advancing technology to provide convenience and comfort through the development of an automation system at home in the form of an automatic gate. The components used for system design are Arduino Uno R3 microcontroller module, HC-05 Bluetooth module, Piezoelectric vibration sensor, DC motor, Power Bank with a capacity of 5600 mAh and a smartphone based on Android version 4.2.1, while the software design uses Arduino IDE, Android SDK and Eclipse IDE. Based on the measurement and test results.